Experimental study on fire extinguishing efficiency of polymer hydrogel fire extinguishing agent in pine-fir mixed coniferous forest fires - Zhangyin Dai; Congbao Huang; Youcheng Chen; Manyin Zhong; Wenwu He (Case Studies in Thermal Engineering)
Pine and fir wood is commonly used in furniture, gardening and construction industries, and has high economic value. It is in great demand in the timber industry. Therefore, pine and fir trees are now widely planted in China. However, pine and fir trees belong to flammable species, with a high content of oil and grease, and the ignition point of pine and fir leaf litter is extremely low. Once burning occurs, it spreads rapidly and can easily turn into a major forest fire. Therefore, the use of extinguishing agents to mitigate and prevent the spread of forest fires is of great importance. In this paper, fire and extinguishing tests were investigated using mixed wood stack burning of pine and fir and mixed fuel from leaf litter. The suppression effects of three different extinguishing agents, AFFF, CAF and hydrogel, on wood fires and leaf litter combustion were compared. And the suppression supply strength of different extinguishing agents to suppress pine and fir trees was determined. The results show that both hydrogel and CAF can effectively extinguish wood stack fires, and AFFF shows re-ignition phenomenon after extinguishing wood stack fires; Comparison of extinguishing time, cooling rate and heat dissipation capacity revealed that hydrogel was superior to CAF; Hydrogel has a highly efficient fire extinguishing properties. It is calculated that the amount of hydrogel used to extinguish pine and cedar fires is only 54 % of the water required, about 87 % of the amount of Class A foam required under the same circumstances, and about 79 % of the amount of aqueous film-forming foam required; Compared with the foam extinguishing agent, the hydrogel extinguishing agent showed better cooling effect, less extinguishing agent dosage, and shorter extinguishing time of 11 s when extinguishing fires in leaf litter; For the rapid spread of leaf litter combustion and easy to re-ignite characteristics, hydrogel has a significant anti-reignition effect.